New challenges in the study of lithic raw materials in central Italy at the dawn of metal working societies: La Pietra and other radiolarite quarry-workshops in Tuscany (Journal of Lithic Studies, 2016)
In central-southern Tuscany radiolarite has been used as a lithic raw material throughout prehistory. During the Copper Age it was selected for the local production of leaf-shaped artefacts. In the area considered, the Copper Age record is almost totally restricted to burials and virtually no settlements have been investigated so far. Radiolarite artefacts are found mostly as refined arrow and, possibly javelin, heads used as grave goods.Within this context, the discovery and recent investigation of the large radiolarite quarry of La Pietra (Roccastrada, Grosseto) and of the related workshops is of great interest. Our aim here is to integrate the record from this site with other contemporary evidence of radiolarite exploitation. A programme of surveys has thus begun on the other radiolarite outcrops of the area in order to verify the existence of further rock quarrying or working. The discovery of a previously unknown quarry-workshop and two previously unknown workshops on radiolarite outcrops is presented here for the first time. The geological and archaeological data coming from the quarry-workshops will be used, in a future stage of research, to source the radiolarite artefacts found in Copper Age graves of Central Italy. The Copper age armatures are valuable artefacts mostly kept in museums and fully non-destructive analyses must be applied to them. To tackle these challenges, we followed a methodological approach which integrates field surveys, the individuation of petrographic markers of the most exploited radiolarite horizons and geochemical analyses. For geochemical characterization, we made use of pXRF portable spectrometer and here we present some preliminary results in the light of current methodological debate.In conclusion, even if some methodological questions remain open, we verified the feasibility of this programme of geographical, geological and geochemical characterizations and need now to increase our dataset in order to reconstruct a viable picture of Copper age lithic economy in central-southern Tuscany.